2016
DOI: 10.1093/mmy/myw028
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of virulence factors andin vivobiofilm-forming capacity ofYarrowia lipolyticaisolated from patients with fungemia

Abstract: Yarrowia lipolytica is ubiquitous in the environment, opportunistic, and might be considered as one of the causative agents of catheter-related candidemia. Our work aimed to study some virulence factors of Y. lipolytica such as hydrolases production and biofilm formation with comparison to the most frequent Candida specie in human disease. In sum, 58 clinical isolates of Y. lipolytica, 16 C. glabrata, and 12 C. albicans were collected from Intensive care unit (ICU). All were tested for enzymatic production and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
5
14
0
Order By: Relevance
“…Caseinase activity was not detected under the employed experimental conditions for any of the tested C. glabrata strains. However, these results were discordant from those found by Abbes et al [53] who reported caseinase activity in 16 C. glabrata isolates. Secretion of caseinase has also been observed in Candida parapsilosis sensu stricto [24], Candida haemulonii species complex [54], and Yarrowia lipolytica [53].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Caseinase activity was not detected under the employed experimental conditions for any of the tested C. glabrata strains. However, these results were discordant from those found by Abbes et al [53] who reported caseinase activity in 16 C. glabrata isolates. Secretion of caseinase has also been observed in Candida parapsilosis sensu stricto [24], Candida haemulonii species complex [54], and Yarrowia lipolytica [53].…”
Section: Discussionsupporting
confidence: 54%
“…However, these results were discordant from those found by Abbes et al [53] who reported caseinase activity in 16 C. glabrata isolates. Secretion of caseinase has also been observed in Candida parapsilosis sensu stricto [24], Candida haemulonii species complex [54], and Yarrowia lipolytica [53]. Pärnänen et al [55] identified a serine protease in C. glabrata linked to the fungal cell wall, but its role in virulence of C. glabrata remains uncertain.…”
Section: Discussionsupporting
confidence: 54%
“…Hydrolytic enzymes are one of the major factors, which could affect the pathogenicity of Y. lipolytica . This fungus is able to produce wide range of hydrolases, such as: proteases, phospholipases and hemolysins, which help in the invasion of tissues (Abbes et al 2017 ; Kantarcioglu and Yucel 2002 ). Phospholipases and proteases secreted by yeasts play an important role in the damage of cell membranes, which consist of lipids and proteins.…”
Section: Virulence Factors Of Y Lipolyticamentioning
confidence: 99%
“…In another research 58 Y. lipolytica isolates of blood, urine and vaginal origin were evaluated to produce hydrolytic enzymes in comparison with C. albicans and C. glabrata . 98.2% of Y. lipolytica isolates showed caseinase activity and only vaginal isolates showed phospholipase activity and the hemolytic activity between the three species showed no significant differences (Abbes et al 2017 ).…”
Section: Virulence Factors Of Y Lipolyticamentioning
confidence: 99%
See 1 more Smart Citation